Optimizing livestock farming in urban agriculture - Grace, Delia; Cook, Elizabeth A.J.; Lindahl, Johanna F. (Burleigh Dodds Science Publishing Limited, 2020)
This chapter summarizes the importance of urbanization and how this increases the consumption of livestock products (LP). This increased demand, alongside infrastructure challenges making transporting and storing LP challenging, encourages urban livestock, close to the final consumer. While data on urban livestock keeping is limited, substantive evidence indicates that large numbers of livestock are kept, and that many processing and retailing activities occur in cities. Key issues for urban livestock keeping are related to human health, nutrition, environment, economy and ethics, and while it has many benefits, it is also implicated in significant problems. The chapter describes these in depth, with reviews of key research. The importance of research in optimizing urban livestock systems is demonstrated by a case study from Nairobi. The chapter concludes with a section on how research can contribute to enhanced, sustainable livestock keeping in cities, followed by a guide to finding additional information and references.